The New Law Library of the University of Zurich - Strehler, René; Niederer, Ulrich (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2006)
The article presents the new Law Library that was opened to the public in 2004. It was integrated in the courtyard of an existing building; its creator was the engineer and architect Santiago Calatrava. The article touches first on the historical background of the building, then gives an outline of the project development. It goes on to explain some of the ecological and energy-saving measures and finally demonstrates the building itself; as the building cannot be ’explained’ the demonstration comes in the form of a running commentary on the slides that were shown at the presentation during the LIBER Architecture seminar in Utrecht. The presentation itself is on the web: href="http://www.zhbluzern.ch/LIBER-LAG/PP_LAG_06/Thursday/Strehler_ZH-RWI-oA.pdf" René Strehler was project manager for the Building Department of the Canton of Zurich, during the construction activities. The Building Department of the Canton of Zurich acted on behalf of the Law Faculty of the University of Zurich.